2020
DOI: 10.1177/2192568220948475
|View full text |Cite
|
Sign up to set email alerts
|

“Law of Temporary Diminishing Distraction Gains”: The Phenomenon of Temporary Diminished Distraction Lengths With Magnetically Controlled Growing Rods That Is Reverted With Rod Exchange

Abstract: Study Design: Prospective study. Objectives: To study the increasing divergence between targeted and achieved distractions observed with magnetically controlled growing rod (MCGR)lengthening, and the relationship of this reduced rate of achieved lengthening with remaining rod length. Methods: Patients with early onset scoliosis (EOS) who underwent MCGRs with minimum 2-year follow-up were consecutively enrolled. Targeted and achieved lengths were compared. Correlation between percentage of lengthening achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
10
1
1
Order By: Relevance
“…The mechanistic reason for MCGR stalling is not well understood in the literature. A postulate is that the magnetic actuator generates an insufficient force to continue to lengthen the spine over time with successive lengthening sessions resulting in decrease yield or complete failure to lengthen [ 9 , 11 , 12 ]. This “law of diminishing returns” has been proposed to represent progressive stiffness or even auto-fusion of spanned spinal segments over the treatment course [ 11 ], as has been reported in the TGR literature [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanistic reason for MCGR stalling is not well understood in the literature. A postulate is that the magnetic actuator generates an insufficient force to continue to lengthen the spine over time with successive lengthening sessions resulting in decrease yield or complete failure to lengthen [ 9 , 11 , 12 ]. This “law of diminishing returns” has been proposed to represent progressive stiffness or even auto-fusion of spanned spinal segments over the treatment course [ 11 ], as has been reported in the TGR literature [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This “law of diminishing returns” has been proposed to represent progressive stiffness or even auto-fusion of spanned spinal segments over the treatment course [ 11 ], as has been reported in the TGR literature [ 13 , 14 ]. However, it has also been reported that this diminished distraction gain is rather a progressive failure of magnetic actuator that is reversed with MCGR exchange [ 12 ]. Explant analysis of MCGR implants have identified that duration of implantation is directly correlated with the extent of lengthening with implanted MCGRs of greater duration being significantly less likely to be functional at the time of explant [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Long-term studies have shown a similar concept of diminishing returns that is inherent to the rod rather than the patient. 15 Cheung et al 15 illustrated increasing mismatch between the intended and observed lengthening of the rods with increasing lengthening, which is reset with rod exchange. In addition, Rushton et al 16 tested the force generated by the rods with correlation to the time from implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cheung et al proposed the “law of temporary diminishing distraction gains” for monthly distracted MCGRs, which suggests diminishing distraction length gain is independent of patient factors, and normal distraction length is again achieved after rod exchange. 14,54 Whether these findings apply to clinicians who distract on a three- or six-monthly basis remains to be seen. Our study demonstrated that neither lengthening regimen increases off-loading from the spine compared to the other; however, damage to the spine’s tissues was observed when larger lengthening regimens were applied.…”
Section: Discussionmentioning
confidence: 99%